Launching a Geriatric Surgery Center: Recommendations from the Society for Perioperative Assessment and Quality Improvement. Issue 9 (13th July 2020) - Cooper, Lisa; Abbett, Sarah K.; Feng, Aiden; Bernacki, Rachelle E.; Cooper, Zara; Urman, Richard D.; Frain, Laura N.; Edwards, Angela F.; Blitz, Jeanna D.; Javedan, Houman; Bader, Angela M.
Abstract : To prepare for the increasing numbers of older adults undergoing surgery, the American College of Surgeons (ACS) has recently launched the Geriatric Surgery Verification Program with the goal of encouraging the creation of centers of geriatric surgery. Meanwhile, the Society for Perioperative Assessment and Quality Improvement (SPAQI) has published recommendations for the preoperative management of frailty, which state that teams should actively screen for frailty before surgery and that pathways, including geriatric comanagement, shared decision‐making, and multimodal prehabilitation, should be embedded in routine care to help improve patient outcomes. Both SPAQI and the ACS advocate for a multidisciplinary approach to improve the value of care for older adults undergoing surgery. However, the best way to implement geriatric services in the surgical setting is yet to be determined. In this statement, we will describe the SPAQI recommendations for launching a geriatric surgery center and the process by which its value should be assessed over time.